Global Lipschitz stability estimates for polygonal conductivity inclusions from boundary measurements. Issue 10 (3rd July 2022) - Beretta, Elena; Francini, Elisa
Abstract : We derive Lipschitz stability estimates for the Hausdorff distance of polygonal conductivity inclusions in terms of the Dirichlet-to-Neumann map.